Deciphering the therapeutic potential of trimetazidine in rheumatoid arthritis via targeting mi-RNA128a, TLR4 signaling pathway, and adenosine-induced FADD-microvesicular shedding: In vivo and in silico study - Omran, Enas; Alzahrani, Abdullah R.; Ezzat, Samar F.; Ellithy, Ghada; Tarek, Marwa; Khairy, Eman; Ghit, Mohamed M.; Elgeushy, Ahmed; Ibrahim Al-Hazani, Tahani Mohamed; Aziz Ibrahim, Ibrahim Abdel; Falemban, Alaa Hisham; Bamagous, Ghazi A.; et al. (Frontiers in Pharmacology, 2024)
Rheumatoid arthritis (RA) is a debilitating autoimmune condition characterized by chronic synovitis, joint damage, and inflammation, leading to impaired joint functionality. Existing RA treatments, while effective to some extent, are not without side effects, prompting a quest for more potent therapies. Re-cent research has unveiled the critical role of FAS-associated death domain protein (FADD) microve-sicular shedding in RA pathogenesis, expanding its scope beyond apoptosis to encompass inflammatory and immune pathways. This study aimed to investigate the intricate relationship between mi-RNA 128a, autoimmune and inflammatory pathways, and adenosine levels in modulating FADD expression and microvesicular shedding in a Freund's complete adjuvant (FCA)-induced RA rat model and further ex-plore the anti-rheumatoid potency of trimetazidine (TMZ). The FCA-treated model exhibited signifi-cantly elevated expression levels of serum fibrogenic, inflammatory, immunological, and rheumatolog-ical diagnostic markers, confirming successful RA induction. Our results revealed that the FCA-induced RA model displayed a significant reduction in paw tissue FADD expression and increased FADD-microvesicular shedding in synovial fluid which was attributed to the significant elevation in the expression of epigenetic miRNA 128a gene alongside the downregulation of adenosine levels. These findings were further supported by the significant activation of the TLR4/MYD88 pathway and their downstream inflammatory IkB/NFkB markers. Interestingly, administration of TMZ significantly ame-liorated, with a similar potency as methotrexate (MTX), the deterioration effect of FCA treatment as evidenced by a significant attenuation of fibrogenic, inflammatory, immunological, and rheumatological markers. Our investigations indicated that TMZ uniquely acted by targeting the epigenetic miRNA128a expression, and elevating the adenosine levels in paw tissue, leading to increased paw tissue FADD expression and mitigated FADD-microvesicular shedding in synovial fluid. Furthermore, the TMZ-treated group displayed significant downregulation of TLR4/MYD88 and their downstream TRAF6, IRAK, and NF-kB. Taken together, our study unveils the significant potential of TMZ as an an-ti-rheumatoid candidate, offering anti-inflammatory effects through various mechanisms, including modulation of the FADD-epigenetic regulator mi-RNA 128a, adenosine levels, and TLR4 signaling pathway in joint tissue, but also attenuation of FADD-microvesicular shedding in synovial fluid. These findings further highlight the synergistic administration of TMZ and MTX as a potential approach to reduce MTX's adverse while enhancing therapeutic efficacy.